Double-Layer Membranes of Chitosan and Sodium Alginate Added to Natural Olive Leaf Extract for Potential Use in Skin Lesions - Larah Gondim Santos Paulino; Luisa Bataglin Avila; Caroline Costa Moraes; Mohammad Rizwan Khan; Salim Manoharadas; Glaydson Simões dos Reis; Guilherme Luiz Dotto; Gabriela Silveira da Rosa (Resources, 2023)
This study seeks to enhance bilayer membranes using a combination of chitosan and sodium alginate (CS/SA) with phytochemical compounds extracted from olive leaves (CS/SA-OLE), intended for use as a skin dressing. Olive leaf extracts (OLE) were sustainably obtained and showed a phenolic composition of 114.49 mgGAE·g−1 and antioxidant activity of 94.25%. CS/AS and CS/SA-OLE were prepared using the casting method. The results showed that the addition of OLE improved the mechanical and barrier properties of the membranes. The elongation at break increased from 9.99 to 14.68%, and the water transmission rate reduced from 2207.78 to 2094.33 (g·m−2·24 h−1) after the addition of OLE. The FTIR spectra showed functional groups of phenolic compounds, and the thermogravimetric analysis showed that the addition of OLE improved the thermal stability of the membranes. In addition, the CS/SA-OLE membranes showed active potential with inhibition halos (12.19 mm) against the microorganism Escherichia coli. The membranes generated in this research, particularly those with the addition of natural extracts, exhibit significant promise for utilization as wound dressings.